2022
DOI: 10.1186/s10020-022-00494-5
|View full text |Cite
|
Sign up to set email alerts
|

Oxalate-induced apoptosis through ERS-ROS–NF-κB signalling pathway in renal tubular epithelial cell

Abstract: Background Kidney stones are composed of approximately 70–80% calcium oxalate. However, the exact mechanism of formation of calcium oxalate kidney stones remains unclear. In this study, we investigated the roles of endoplasmic reticulum stress (ERS), reactive oxygen species (ROS), and the NF-κB signalling pathway in the pathogenesis of oxalate-induced renal tubular epithelial cell injury and its possible molecular mechanisms. Methods We established… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 49 publications
0
18
0
Order By: Relevance
“…The results indicating that apoptosis is close with the disruption of CL. Moreover, an increasing amount of research has demonstrated that LTB 4 can serve as a trigger for apoptosis (Mangolini et al, 2010; Ming et al, 2022). It implies that there are likely multiple mechanisms involved in the activation of caspase in response to CDCT exposure.…”
Section: Discussionmentioning
confidence: 99%
“…The results indicating that apoptosis is close with the disruption of CL. Moreover, an increasing amount of research has demonstrated that LTB 4 can serve as a trigger for apoptosis (Mangolini et al, 2010; Ming et al, 2022). It implies that there are likely multiple mechanisms involved in the activation of caspase in response to CDCT exposure.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the stimuli described above, reactive oxygen species (ROS) is a potent inducer mediating EMT particularly in peritubular microenvironment (Figure 3). The increased level of intracellular ROS can cause oxidation of lipids, DNAs, and proteins, leading to cell damage/injury (Ming et al, 2022; Wu et al, 2023). ROS also acts as a secondary messenger in cellular signaling pathways (Ming et al, 2022; Wu et al, 2023).…”
Section: Emt and Kidney Fibrosismentioning
confidence: 99%
“…The increased level of intracellular ROS can cause oxidation of lipids, DNAs, and proteins, leading to cell damage/injury (Ming et al, 2022; Wu et al, 2023). ROS also acts as a secondary messenger in cellular signaling pathways (Ming et al, 2022; Wu et al, 2023). When ROS increases in TECs, the cells release proinflammatory cytokines and chemokines for repairing mechanism.…”
Section: Emt and Kidney Fibrosismentioning
confidence: 99%
See 1 more Smart Citation
“…Further, it has been demonstrated that HS increases NF-κB and interleukin-1β (IL-1β) expression and participates in the inflammatory response. , Overactivation of the UPR cascades is considered to be a major cause of inflammatory response in the gut. The three UPR signalings of ERS can activate the NF-κB pathway; for example, IRE1α/TRAF2 can evoke NF-κB via Nucleotide Binding Oligomerization Domain Containing 1/2 (NOD1/NOD2), while phosphorylated eIF2α activates the NF-κB pathway by inhibiting the synthesis of inhibitor of κB (IκB) . Recent research has also revealed an involvement of ROS in NF-κB signaling initiation via IκB phosphorylation .…”
Section: Crosstalk Between Ers and Oxidative Stress Controls Cell Fat...mentioning
confidence: 99%